2014
DOI: 10.1007/s10067-013-2468-z
|View full text |Cite
|
Sign up to set email alerts
|

Revising DAS28 scores for remission in rheumatoid arthritis

Abstract: Current initiatives to treat rheumatoid arthritis (RA) to target remission have resulted in the widespread use of composite outcome measures to quantify disease activity. Simplified Disease Activity Index (SDAI) ≤3.3 is the gold standard of remission. Previous work has suggested that the remission threshold of DAS28-ESR or DAS28-CRP ≤2.6 is known to be not strict enough and should be revised. There is no previous study that looks at the equivalent DAS28-CRP value that best reflects SDAI remission in a real-lif… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
20
0
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 24 publications
(22 citation statements)
references
References 19 publications
1
20
0
1
Order By: Relevance
“…Matsui et al suggested that DAS28-CRP underestimated disease activity. Inoue et al found DAS28-CRP 2.3 matched DAS28-ESR remission in Japanese patients [10].The present study suggests that composite scores overestimate remission and patients retain subclinical inflammation found on MRI. Our results join the various studies that have proven the dissociation between clinical remission according different composite scores and remission in imaging either by ultrasound (Ramirez J et al [11]) or MRI (Gandjbakhch F et al [12]) or both (Foltz V et al [13]).…”
Section: M6 P Referencessupporting
confidence: 55%
See 1 more Smart Citation
“…Matsui et al suggested that DAS28-CRP underestimated disease activity. Inoue et al found DAS28-CRP 2.3 matched DAS28-ESR remission in Japanese patients [10].The present study suggests that composite scores overestimate remission and patients retain subclinical inflammation found on MRI. Our results join the various studies that have proven the dissociation between clinical remission according different composite scores and remission in imaging either by ultrasound (Ramirez J et al [11]) or MRI (Gandjbakhch F et al [12]) or both (Foltz V et al [13]).…”
Section: M6 P Referencessupporting
confidence: 55%
“…There are several composite measures which correlate well, higher values having poor functional and radiologic outcomes, but there remains disagreement in classifying disease activity states. Disease activity score assessing 28-joint (DAS28) versions using erythrocyte sedimentation rate (ESR) and C-reactive protein (CRP) have good correlation but not equivalence but it's overestimated remission compared to all other criteria [10]. The American college of rheumatology (ACR) and the European league against rheumatism (EULAR) have defined remission as a simplified disease activity index (SDAI) value of ≤ 3.3 (index-based definition).…”
Section: M6 P Referencesmentioning
confidence: 99%
“…Remission can currently be confirmed when the DAS28 score is lower than 2.4, or confirmed independently using the 2010 American College of Rheumatology (ACR)/EULAR criteria 7,17,20. Although both rules share common items, discrepancies exist and the need for guidelines has been pointed out 21. Shaver et al already reported some inconsistencies using published cut-offs for remission of DAS28 and CDAI and therefore recommend cautious use of these with patients 22…”
Section: Review Of Methodological Issuesmentioning
confidence: 99%
“…Erste Daten zeigen, dass bei einem frühzeitigen Therapiebeginn bei einigen Patienten sogar arzneimittelfreie Intervalle erreichbar sind [18]. [24,25]. Zur Therapieanpassung stehen v. a. für die Behandlung von RA-Patienten zahlreiche altbewährte, aber auch moderne Medikamente wie Biologika und aktuell BiosiAbb.…”
Section: Treat-to Target: Verbesserung Der Prognose Durch Früh-erkennunclassified